Risk Factors Of Chronic Energy Lack In Pregnant Women - Tamara Maudya Indah Fiari; Suprida Suprida; Yulianto Yulianto (Poltekkes Kemenkes Palembang, 2021)
Background During pregnancy, the mother's body metabolism will increase to support fetalgrowth and development, increase in uterine organs, and changes in bodycomposition and metabolism mother. Therefore, the need for energy and othernutrients will also increase during pregnancy. If the nutritional status of themother is less supportive, pregnant women will experience nutritional problemssuch as chronic energy deficiency (KEK) and nutritional anemia (Handayani &Budianingrum, 2011).Objective: To determine the risk factors for the occurrenceof chronic energy deficiency in pregnant women in the work area of thePalembang Superintendent Health Center in 2021. Methods: The design of thisstudy was case-control. This research was conducted at the Pembina PublicHealth Center of Palembang City. The research sample was 60 first-trimesterpregnant women who were divided into 2 groups, namely the case group and thecontrol group. Results: Based on the results of the statistical test Chi-Square, itwas found that there was a significant relationship between parity with p = 0.001(OR = 7.5, 95% CI: 2.244-25.062) and pregnancy interval with a value of p =0.000 (OR = 16, 4, 95%CI: 4,569-59,073) with the risk of Chronic EnergyDeficiency in pregnant women. Conclusion: There is a relationship betweenparity & pregnancy distance to the incidence of chronic energy-deficientpregnant women at Pembina Puskesmas Palembang in 2021. Pregnant womenwith risk parity (> 2 children) are 7.5 times at risk of experiencing chronicenergy deficiency and pregnant women with risky pregnancy intervals ( < 2years) 16.4 times the risk of experiencing chronic energy deficiency. Keywords: Risk of Chronic Energy Deficiency, Pregnant Women